Implementation of Social Educational Values in the Pillars of Islam at Pondok Pesantren Miftahussa’adah Sindangbarang - Mukhlisin Mukhlisin; Malik Sofy; Deden Purbaya; Ahmad Rifai (STAI Al-Mas'udiyah, 2024)
This study aims to identify the social education values within the Five Pillars of Islam, their implementation, and their outcomes in the lives of students at Pondok Pesantren Miftahussa’adah. The research indicates that social education values in the Five Pillars include fostering trust in others' potential, thoughts, and responsibilities, maintaining cleanliness, discipline, orderliness, consistent concern for others, refraining from causing harm, and preserving social ties with any community. The implementation of social education values at Pondok Pesantren Miftahussa’adah includes communal prayers, recitations of Ratib and Yasin, Sholawat, tahlil, and commemorating the founders of the school. The outcomes of implementing social education values from the Five Pillars in the lives of the students at Pesantren Miftahussa’adah are increased awareness and concern for others, mutual respect and trust, collaborative decision-making, and maintaining a clean environment.